Evaluation the professional Practice of community pharmacists in dealing with important drug interactions in prescription - Amir Larki-Harchegani, Maryam Mehrpooya, Amjad Qadermazi, Somayeh Shabib , Sara Ataei (Journal of Applied Pharmaceutical Science, 2018)
Introduction: Pharmacists play an important role in promoting the public health by optimizing the use of medications through effective communication between the patient and the physician. It is important to assess the scientific capability and accuracy of pharmacists in identifying and correcting possible drug errors in the manuscript. The purpose of this research is to assess the extent of success of pharmacists in performing their professional tasks and determine the important factors involved in this issue. Methods: In this descriptive cross-sectional study, 82 pharmacies were selected to be assessed on their performance in Hamadan city. A trained person with a prescription containing important drug interactions presented to the pharmacies. After delivering the prescription to the pharmacist, a questionnaire was used to assess the levels of pharmacists’ participation in drug consulting. Results: The results of this study indicated that pharmacists were present only in 67 pharmacies (81.7%). 27 pharmacists (40.3%) asked the patient’s reason for visiting a physician. 22 pharmacists (32.8%) paid attention to the drug interactions with warfarin. 63 pharmacists (94.0%) gave advice about the proper time of drug taking. Conclusions: Although the pharmacists have sufficient knowledge, they showed poor attention and this issue must strongly be considered.
Keywords: Drug interactions, pharmacists, drug consulting, Prescription, Iran.